Reliability Analysis of Randu Garut 3 Distribution System Using Section Technique Method - Jimmy Trio Putra; Raka Bagus (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
In a distribution system, reliability index is significant to calculate system performance in continuosly distribute the electricity power to consuments. Fedeer analysed by researcher is the main electricity distributor in Tambak Aji industrial area, a developing industrial area. This research is needed to be conducted to ensure the frequent blackout is known and minimalized along with increasement of load number in the feeder. Using section technique method which divides feeder section based on sectionalizer number and detailed calculation in each load point, device failure rate, the length of conductor, and disturbance repairement duration. It was obtained Randu Garut 3 feeder reliability index of SAIFI of 1.759 faults/year, SAIDI of 4.547 hours/year as CAIDI of 2.585 hours/year.